Does the angle of seismic incidence affect inelastic seismic demand? A probabilistic point of view - Despoina Skoulidou (2018)
Probabilistic analysis allows taking into account uncertainties that deterministic approaches usually don't permit. In this context, the uncertainty of the angle of seismic incidence is addressed and its effect on the seismic demand of buildings is examined in a probabilistic framework. Buildings comprising different configurations in-plan and in-elevation are subjected to nonlinear time history analysis with forty bi-directional ground motions. The ground motions are applied along twelve angles of incidence, which are sampled from a uniform distribution, and are further re-sampled into groups of different sizes. The seismic demand distributions of samples derived from different ground motion group sizes applied along different number of angles of incidence are compared to the demand distribution of the reference case considered to be the true demand distribution. The results show that considering more than one angle of seismic incidence always improves the result. The effect of the angle seems to be dependent on the size of the ground motion group and, from a probabilistic point of view, considering more than five angles of incidence has no significant effect on the seismic demand.